A dance with dragons - Martin, George R. R. (Martin, George R. R. Song of ice and fire, 2011)
New threats emerge to endanger the future of the Seven Kingdoms, as Daenerys Targaryen, ruling in the East, fights off a multitude of enemies, while Jon Snow, Lord Commander of the Night's Watch, faces his foes both in the Watch and beyond the great Wall of ice and stone.